The Relationship between Poetry and Music in the Mélodies of Reynaldo Hahn - Karácsony, Noémi (Babes-Bolyai University Cluj-Napoca, 2019)
The present paper aims to reveal some of the features which characterize the Mélodies of the French composer Reynaldo Hahn. Although his work comprises several genres, instrumental and vocal alike, these refined and sensitive vocal miniatures are most often associated with Hahn’s name. Composer, conductor and music critic, himself a singer, the fascinating personality and intelligence of the composer is reflected in his works. His Mélodies mirror Hahn’s preoccupation regarding the relationship between poetry and music, between the spoken and the sung words. In the master’s opinion, music should emphasize the deep, hidden meanings beyond the words, thus in his vocal miniatures he strives for a truthful evocation of that which remains unspeakable.
Keywords: Reynaldo Hahn; French; poetry; Mélodie